1996
DOI: 10.1097/00007632-199608150-00018
|View full text |Cite
|
Sign up to set email alerts
|

Semirigid Instrumentation in the Management of Lumbar Spinal Conditions Combined With Circumferential Fusion

Abstract: This technique produces a satisfactory fusion rate (97%) and a good clinical outcome based on pain reduction and return to a satisfactory level of activity (77%). It is associated with few, but significant, complications that compare well with other reported series in a difficult group of patients. This procedure should be reserved for patients who are considered to be at high risk for not achieving spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 9 publications
0
55
0
5
Order By: Relevance
“…Kuslich et al [28] reported a 91% fusion rate, 84% pain relief and 91% functional improvement at 24 months' follow-up using the BAK method of lumbar interbody fusion. Other authors [1,2,3,10,16,50,52] have reported more than 70% satisfactory clinical results with instrumented interbody fusion. Our patients had a 72% rate of clinical satisfaction with ALIF and 74% with circumferential fusion (PLIF) using subjective scores, and 79.5% and 80% clinical satisfaction using the Oswestry Disability Index.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kuslich et al [28] reported a 91% fusion rate, 84% pain relief and 91% functional improvement at 24 months' follow-up using the BAK method of lumbar interbody fusion. Other authors [1,2,3,10,16,50,52] have reported more than 70% satisfactory clinical results with instrumented interbody fusion. Our patients had a 72% rate of clinical satisfaction with ALIF and 74% with circumferential fusion (PLIF) using subjective scores, and 79.5% and 80% clinical satisfaction using the Oswestry Disability Index.…”
Section: Discussionmentioning
confidence: 96%
“…PLIF offers several advantages [1,10,16,50,52]. It restores disc height, the load bearing ability of anterior ligaments and muscles, root canal dimensions, and spinal balance.…”
Section: Introductionmentioning
confidence: 99%
“…The radiological results were all assessed in a similar way using the method described by Gertzbein et al [17]. Briefly, fusion was considered solid if the anterior interbody area was fused, if the two posterolateral areas were fused, or if all three areas were fused.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…Note that the implant in use must not be confused with mere "tension-band" augmentation [6,15]. The biomechanical characteristics of semi-rigid implants for lumbar fusion purposes currently available on the market have occasionally featured at least as a partial aspect of clinical papers [4,12,13,17,25,27] and, thus, should briefly be reiterated.…”
Section: Biomechanicsmentioning
confidence: 99%